Introduction: The Startup Process - Acs, Zoltan (Estudios de Economía, 2016)
Entrepreneurship is considered to be an important mechanism for economic development through employment, innovation and welfare effects. The papers in this special issue are from the 3rd Global Entrepreneurship Monitor Research Conference held in Washington D.C. in 2007. The introduction has three objectives. First, to discuss the importance of the three stages of economic development, the factor-driven stage, the efficiency-driven stage and the innovation-driven stage. Second, to examine the empirical evidence on the relationship between stages of economic development and entrepreneurship. Third, to present a summary of the papers.